Psocopterans (Psocoptera: Insecta) from Zapotitlán Salinas, Puebla, Mexico: distribution of abundance and seasonality - José Arturo Casasola-González; Alfonso Neri García-Aldrete; María del Carmen Herrera-Fuentes (Revista Mexicana de Biodiversidad)
A survey of psocopterans in the Zapotitlán Salinas Valley, Puebla, was conducted from October 1994 toOctober 1995. A total of 582 specimens were collected, representing 25 species, belonging to 15 genera and 8 families(18.38% of the species recorded in the state of Puebla). Six species constitute 67% of the total of specimens collected,and 9 species represent 3.4% of the same total. Twelve species were associated to thorn scrub, 16 were found on izotal,and 6 species were found on Bursera spp. trees. It was found that both richness of species and relative abundance arerelated to the rainfall regime of the area (r= 0.595 and r= 0.739, respectively).